Review of the Sonication-Assisted Exfoliation Methods for MoX2 (X: S, Se, Te) Using Water and Ethanol - WANG, Sihan; YU, Yanshu; MENG, Jianling (Archives of Acoustics, 2025)
Two-dimensional transition metal dichalcogenides (MoX2, where X = S, Se, Te), have been the research hotspot over the past decade. The sonication-assisted liquid-phase exfoliation method is suitable for the mass production of MoX2 in practical applications. Water and ethanol, rather than organic solvents, are increasingly chosen for liquid-phase exfoliation method due to their non-toxic, environmentally friendly properties. However, a systematic review of the method for MoX2 preparation using water and ethanol is lacking. In this paper, recently published work on the sonication-assisted exfoliation method for MoX2 preparation using water and ethanol is summarized. Three key parameters are focused on: solvents selection, sonication power, and sonication time. Finally, the application of MoX2 flakes and the future outlook of the sonication-assisted liquid-phase exfoliation method using water and ethanol are presented. The review aims to provide guidance on exfoliating MoX2 using the sonication-assisted exfoliation method with water and ethanol.